2018
DOI: 10.1093/aob/mcy018
|View full text |Cite
|
Sign up to set email alerts
|

DigR: a generic model and its open source simulation software to mimic three-dimensional root-system architecture diversity

Abstract: DigR is based on plant architecture analysis which leads to specific root type classification and organization that are directly linked to field measurements. The open source simulator of the model has been included within a friendly user environment. DigR accuracy and versatility are demonstrated for growth simulations of complex root systems for both annual and perennial plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…The root anatomy is the result of a generative algorithm and is fixed in time. One possible improvement to GRANAR would be to include a developmental module within the model, similar to the current root architectural models (Postma et al, 2017;Barczi et al, 2018;Schnepf et al, 2018). This would allow the model to create root anatomies for different root ages in one simulation, enabling the estimation of the evolution of the root conductivity with the root maturation.…”
Section: Discussionmentioning
confidence: 99%
“…The root anatomy is the result of a generative algorithm and is fixed in time. One possible improvement to GRANAR would be to include a developmental module within the model, similar to the current root architectural models (Postma et al, 2017;Barczi et al, 2018;Schnepf et al, 2018). This would allow the model to create root anatomies for different root ages in one simulation, enabling the estimation of the evolution of the root conductivity with the root maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Mommer et al, 2016), FSP modelling of roots and soils has been gaining momentum. In this issue, new root modelling frameworks are presented that allow for easy simulation of root growth and development over time for a range of root architectures (Barczi et al, 2018;Schnepf et al, 2018). Particular attention is given in these studies to the ability to couple simulation of root growth to simulations of other relevant components, allowing for, for example, analysis of the effects of below-ground interactions on wholeplant performance.…”
Section: Extending Models Of Plant Architecturementioning
confidence: 99%
“…We found that bio-organic fertilizer (BIO) significantly increased the number, length and density of lateral roots of pear trees, and reduced inter-branching distance ( Fig 3A -C and F), supporting the first hypothesis proposed in this paper. Different orders of lateral roots have different functions; lateral roots less than 2 mm in diameter are the most activate part of the root system [37], playing a key role in absorbing soil nutrients and water [9,27]. We found that while the diameter of 2 nd order and above lateral roots of trees grown in all media was 2 mm or less (Fig 4), the number and length of lateral roots in BIO-CF boxes was significantly higher than that of CF-CF boxes, indicating that the bio-organic/chemical fertilizer combination was particularly conducive to allowing pear roots to occupy a large soil space and thereby improve nutrient absorption efficiency.…”
Section: Bio-cf Had a Significant Synergistic Effect On The Growth Ofmentioning
confidence: 99%